Evaluation of Salivary Procalcitonin and Macrophage Activating Factor in Generalised Chronic Periodontitis Patients with and without Type 2 Diabetes Mellitus - Sindhu Ramarao Ghorpade; Vijayalakshmi Rajaram; Jaideep Mahendra; Burnice Nalinakumari Chelladurai; Ambalavanan Namasivayam (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Periodontitis is a polymicrobial and multifactorial oral disease and is the sixth complication of diabetes mellitus. Early diagnosis is important, and the use of non invasive biomarkers are highly useful for this purpose. The level of Macrophage Activating Factor (MAF) and Procalcitonin (ProCT) corresponds to the intensity of the inflammatory response and the severity of infection; thereby indicating that an increase in concentration or persistence of high values is considered as a prognostic indicator for severity of infection with an adverse outcome. Aim: To assess the periodontal parameters and quantify the levels of MAF and ProCT in saliva samples of generalised chronic periodontitis subjects with and without type 2 diabetes mellitus and to correlate these levels with the periodontal parameters. Materials and Methods: The study was a single centre crosssectional study carried out at the Department of Periodontology, Meenakshi Ammal Dental College and Hospital, Chennai, Tamil Nadu, India, from November 2018 to November 2019. A total of 80 subjects with generalised severe chronic periodontitis were selected and divided into two groups. Group I comprised of 40 subjects who were diagnosed with generalised chronic periodontitis without type 2 diabetes mellitus, whereas group II comprised of 40 subjects with generalised chronic periodontitis who had already been diagnosed with type 2 diabetes mellitus. Periodontal parameters such as Plaque Index (PI), Bleeding on Probing (BOP), Probing Pocket Depth (PPD) and Clinical Attachment Level (CAL) were recorded. The collected samples were subjected to molecular analysis for evaluating ProCT and MAF using Enzyme-Linked Immunosorbent assay (ELISA). Statistical analysis was done using Statistical Package for Social Sciences (SPSS) version 25.1 (Chicago, USA Inc). Student’s Independent t-test was used to compare the mean values for the variables in the control and test group. The Pearson’s correlation test was used to evaluate correlation between all the variables. The p-value <0.05 was set as the level of significance. Results: On comparing the periodontal parameters between group I and group II, there was no significant difference between the groups p-value >0.05. The mean salivary ProCT level in group I and group II was 268.76±152.78 ng/mL and 785.75±244.37 ng/mL, respectively. The mean salivary MAF level in group I and group II was 7.15±2.02 ng/mL and 26.56±9.12 ng/ mL, respectively. On comparing MAF and ProCT value between group I and group II, there was a statistically significant increase in group II (p-value <0.001) and a weak correlation value with the periodontal parameters was seen. Conclusion: There was a significant difference in levels of MAF and ProCT in saliva samples of generalised chronic periodontitis subjects with and without type 2 diabetes mellitus, however the periodontal variables in each group did not correlate with MAF and ProCT